The contrapositive of the sentence \[ \sim p \to q\] is equivalent to:
A. $p \to \sim q$
B. $q \to \sim p$
C. $ \sim q \to p$
D. $ \sim p \to \sim q$
E. $ \sim q \to \sim p$
Answer
Verified
456.9k+ views
Hint:
Given an if-then statement, then some related statements with their names are provided below:
1) In mathematical logic, $ \sim ( \sim p) = p$
2) A statement and its contrapositive are logically equivalent, in the sense that if the statement is true, then its contrapositive is true and vice versa.
3) Since an inverse is the contrapositive of the converse, inverse $ \sim p \to \sim q$ and converse $q \to p$ are also logically equivalent to each other.
Complete step by step solution:
From the definition, the contrapositive of $p \to q$ is $ \sim q \to \sim p$
Therefore, the contrapositive of $ \sim p \to q$ will be $ \sim q \to \sim ( \sim p)$
Since, $ \sim ( \sim p) = p$ , therefore $ \sim q \to \sim ( \sim p) = \sim q \to p$.
Therefore, the contrapositive of $ \sim p \to q$ is $ \sim q \to p$ .
The correct answer option is C.
Note:
Logical equivalence is different from material equivalence. Formulas for p and q are logically equivalent if and only if the statement of their material equivalence p ⇔ q is a tautology.
The material equivalence of p and q (often written as p ⇔ q) is itself another statement which expresses the idea “p if and only if q”.
Given an if-then statement, then some related statements with their names are provided below:
Statement | If p, then q. | p → q |
Inverse | If not p, then not q. | $ \sim p \to \sim q$ |
Converse | If q, then p. | $q \to p$ |
Contrapositive | If not q, then not p. | $ \sim q \to \sim p$ |
1) In mathematical logic, $ \sim ( \sim p) = p$
2) A statement and its contrapositive are logically equivalent, in the sense that if the statement is true, then its contrapositive is true and vice versa.
3) Since an inverse is the contrapositive of the converse, inverse $ \sim p \to \sim q$ and converse $q \to p$ are also logically equivalent to each other.
Complete step by step solution:
From the definition, the contrapositive of $p \to q$ is $ \sim q \to \sim p$
Therefore, the contrapositive of $ \sim p \to q$ will be $ \sim q \to \sim ( \sim p)$
Since, $ \sim ( \sim p) = p$ , therefore $ \sim q \to \sim ( \sim p) = \sim q \to p$.
Therefore, the contrapositive of $ \sim p \to q$ is $ \sim q \to p$ .
The correct answer option is C.
Note:
Logical equivalence is different from material equivalence. Formulas for p and q are logically equivalent if and only if the statement of their material equivalence p ⇔ q is a tautology.
The material equivalence of p and q (often written as p ⇔ q) is itself another statement which expresses the idea “p if and only if q”.
Recently Updated Pages
Master Class 11 English: Engaging Questions & Answers for Success
Master Class 11 Computer Science: Engaging Questions & Answers for Success
Master Class 11 Maths: Engaging Questions & Answers for Success
Master Class 11 Social Science: Engaging Questions & Answers for Success
Master Class 11 Economics: Engaging Questions & Answers for Success
Master Class 11 Business Studies: Engaging Questions & Answers for Success
Trending doubts
10 examples of friction in our daily life
What problem did Carter face when he reached the mummy class 11 english CBSE
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
State and prove Bernoullis theorem class 11 physics CBSE
The sequence of spore production in Puccinia wheat class 11 biology CBSE